Dual-Drug Loaded Nanobubbles Combined with Sonodynamic and Chemotherapy for Hepatocellular Carcinoma Therapy - Guo T; Wang Y; Chen D; Cui S; Guo S; Feng Y; Zhu J; Chang L; Zhang J; Gao X; Wei X (International Journal of Nanomedicine, 2024)
Tiantian Guo,1 Yao Wang,1 Dixuan Chen,2 Sifan Cui,2 Shuyue Guo,1 Yixing Feng,1 Jialin Zhu,1 Luchen Chang,1 Jiawei Zhang,2 Xiujun Gao,2 Xi Wei1 1Department of Diagnostic and Therapeutic Ultrasonography, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center of Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin Medical University, Tianjin, 300060, People’s Republic of China; 2School of Biomedical Engineering and Technology, Tianjin Medical University, Tianjin, 300070, People’s Republic of ChinaCorrespondence: Xi Wei, Department of Diagnostic and Therapeutic Ultrasonography, Tianjin Medical University Cancer Institute and Hospital, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin’s Clinical Research Center for Cancer, Huanhuxi Road, Tiyuanbei, Hexi District, Tianjin, 300060, People’s Republic of China, Email weixi@tmu.edu.cn Xiujun Gao, School of Biomedical, Engineering and Technology, Tianjin Medical University, No. 22, Meteorological Station Road, Tianjin, 300070, People’s Republic of China, Email gaoxiujun12242@tmu.edu.cnPurpose: Chemotherapy remains the primary therapeutic approach for advanced Hepatocellular Carcinoma (HCC). The therapeutic effect of chemotherapy is limited and the toxic side effects are serious. The aim of this study is to develop a nanobubble that is ultrasonically responsive to reduce the toxic side effects of direct chemotherapy.Methods: We developed curcumin/doxorubicin-cis-aconitic anhydride-polyethylene glycol nanobubble (C/DCNB) surface modified with acid-sensitive polyethylene glycol (PEG). And it is loaded with curcumin (CUR) and doxorubicin (DOX), as liposomes at the nanoscale for diagnosis and therapy of tumors.Results: In this study, the acid-sensitive PEG on the surface layer of nanobubbles serves to stabilize them in the blood circulatory system and in normal tissues, while peeling off in the acidic tumor microenvironment (pH 6.8). C/DCNB can identify tumor sites through contrast-enhanced ultrasound (CEUS). And ultrasound-mediated nanobubbles promote permeability of the tumor vascular, thus improving the enhanced permeability and retention (EPR) effects in the tumor, leading to the accumulation of nanobubbles in the tumor. After endocytosis of nanobubbles, drugs are released and curcumin generates reactive oxygen species (ROS) under ultrasound conditions. CUR can enhance the sensitivity of tumor cells to DOX by inhibiting the expression of P-glycoprotein. In vitro and vivo experiments demonstrate that C/DCNB can facilitate contrast-enhanced ultrasound imaging while simultaneously delivering drugs, enabling both imaging and treatment.Conclusion: The combination of C/DCNB and ultrasound provides an effective strategy for improving the efficiency of HCC therapy and imaging. Keywords: combination of sonodynamic therapy and chemotherapy, the synergistic effect of two drugs, integration of diagnosis and treatment, ultrasound